2008
DOI: 10.1007/s00213-008-1303-8
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement of ethanol and sucrose seeking by the neurosteroid allopregnanolone in C57BL/6 mice

Abstract: Rationale Recent work in our laboratory documented that the “sipper” method of operant ethanol self-administration produced high ethanol intake and blood ethanol concentrations as well as the typical extinction “burst” in responding under non-reinforced conditions in male C57BL/6 mice. However, the neurochemical basis for reinstatement of responding following extinction has not been examined in mice with this model. Objectives Based on findings that the GABAergic neurosteroid allopregnanolone (ALLO) signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 84 publications
(107 reference statements)
6
32
0
Order By: Relevance
“…Moreover, GABAergic neuroactive steroids, like various drugs of abuse, exhibit rewarding properties in DBA/2J mice and Long-Evans rats (Finn et al 1997a; Sinnott et al 2002) and enhance brain stimulation reward in C57BL/6J mice, much like cocaine (Fish et al, this issue). 3α,5α-THP and other GABAergic neuroactive steroids exhibit biphasic modulation of ethanol intake in various rodent models of ethanol self-administration (Besheer et al 2010; Finn et al 2008; Ford et al 2007; Ford et al 2005; Janak et al 1998; Morrow et al 2001), suggesting complex actions on neuronal circuitry mediating these behaviors. The complexity of these behavioral responses in rodents points to the possibility that genetic variation may play an important role in neuroactive steroid actions across species.…”
Section: Pharmacological Properties Of Neuroactive Steroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, GABAergic neuroactive steroids, like various drugs of abuse, exhibit rewarding properties in DBA/2J mice and Long-Evans rats (Finn et al 1997a; Sinnott et al 2002) and enhance brain stimulation reward in C57BL/6J mice, much like cocaine (Fish et al, this issue). 3α,5α-THP and other GABAergic neuroactive steroids exhibit biphasic modulation of ethanol intake in various rodent models of ethanol self-administration (Besheer et al 2010; Finn et al 2008; Ford et al 2007; Ford et al 2005; Janak et al 1998; Morrow et al 2001), suggesting complex actions on neuronal circuitry mediating these behaviors. The complexity of these behavioral responses in rodents points to the possibility that genetic variation may play an important role in neuroactive steroid actions across species.…”
Section: Pharmacological Properties Of Neuroactive Steroidsmentioning
confidence: 99%
“…It has been suggested that endogenous neuroactive steroids may play a role in ethanol sensitivity in these strains. In fact, 3α,5α-THP modulates ethanol intake (Ford et al 2007; Ford et al 2005), reinstates ethanol seeking behavior in C57BL/6J mice (Finn et al 2008) and affects ethanol withdrawal severity (Finn et al 2004a; Gililland and Finn 2007). …”
Section: Gabaergic Neuroactive Steroids and Ethanol Interactionsmentioning
confidence: 99%
“…Studies also have shown mice responding for ethanol when ethanol reinforcement is continuously available (Risinger, Brown, Doan, & Oakes, 1998), when it is made available for extended periods (~16 h) (Besheer, Lepoutre, & Hodge, 2004; Hodge et al, 2006), and when access is limited for short periods of time (~30–60 min) (Chu et al, 2007; Lopez, Anderson, & Becker, 2008; Lopez & Becker, 2014; Ramaker, Strong, Ford, & Finn, 2012; Sparta et al, 2009; Tsiang & Janak, 2006). Using the ‘sipper’ model described above, mice were shown to reliably respond to gain access to drink ethanol from a bottle made available for 30 min once the response requirement was satisfied (Finn et al, 2008; Ford et al, 2007). In this latter case, manipulating the reinforcement schedule to further separate the appetitive and consummatory components of the procedure enhanced both the appetitive drive to gain access to ethanol (as indicated by reduced latency to fulfill the response requirement) and the consummatory component (increased amount of ethanol consumed).…”
Section: Operant Ethanol Self-administration In Micementioning
confidence: 99%
“…However, previous studies have suggested that allopregnanolone may indeed play a role in EtOH's actions, independent from its steroidogenic effects. In fact, allopregnanolone administration to C57BL/6J mice modulates EtOH self-administration (Ford et al, 2005, 2007) and reinstates EtOH seeking behavior (Finn et al, 2008). Likewise, allopregnanolone administration modulates EtOH self-administration in rats (Janak et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Allopregnanolone modulates EtOH intake (Ford et al, 2005, 2007) and reinstates EtOH seeking behavior in C57BL/6J mice (Finn et al, 2008); it is also thought to modulate EtOH withdrawal severity across mouse strains (Finn et al, 2004a; Gililland and Finn, 2007). Acute EtOH administration increases whole brain allopregnanolone levels in male DBA/2J (Gabriel et al, 2004) and C57BL/6J mice, although in this strain, the effect did not reach statistical significance (Finn et al, 2004b).…”
mentioning
confidence: 99%